Healthy vending and concession initiative and implementation - Hoffman, Scott (My University, 2014)
My field experience work has been extensive and comprehensive, leading me to benefit from a breadth of experiences. I have visited many locations and attended numerous meetings during my field experience. I engaged in many meetings at the Riley County Extension Office at 110 Courthouse Plaza with Ginny Barnard to discuss activities and policy plans to better the community, and I have also attended Flint Hills Wellness Coalition meetings there as well. Through K-State Research and Extension, I had the opportunity to participate in educational programs in many elementary schools in the Riley County area. During those visits, Ginny Barnard, myself, or both of us would teach nutritional lessons. With the Help of Gregg Eyestone, horticulture agent of K-State Research and Extension, we planted and harvested gardens with the elementary students, consisting of 175 fourth graders. For another aspect of my MPH field experience, I was employed as an intern in the Human Resources Department of Manhattan City Hall to help promote healthy vending. My internship opportunity with the City of Manhattan was made possible through Ginny Barnard’s role on the leadership team with the Flint Hills Wellness Coalition. The Flint Hills Wellness Coalition (FHWC) meetings have been held in several different locations, but they are always held with the same mission, to build a healthier community. The FHWC brings prestigious members of the community together to discuss and disseminate public health ideas and information for eventual implementation in the Manhattan area. In addition to all of these locations, I have also made an appearance at the headquarters for Five Star Vending to discuss the main focus of my MPH field experience, the healthy vending initiative. Healthy vending policies in Johnson County, Kansas and other Kansas Communities have become a recent area of interest in light of the overweight and obesity endemic in the United States (2). Johnson County is currently using the same standards in their concession stands and vending machines that the FHWC is trying to implement into the City of Manhattan; they are calling it the “SCORE!” campaign (24). The mission of the Healthy Foods-Johnson County, Kansas Coalition is to provide greater access to healthy foods for their community. The Coalition also promotes policy and environmental changes to support their mission. Healthy vending is not just an interest in the U.S.; a study in Queensland, Australia examined implementations of healthier foods into healthcare facilities via many routes, including vending machines (18). Even schools in the Netherlands recorded an approximate 10% increase in healthy foods held in all vending machines over the past five years. They have also documented an obesity trend in schools with copious amounts of unhealthy vending options (22).
Keywords: Healthy vending; SCORE Campaign; Riley County Kansas; Public Health (0573)